Complete Tri Symptomatic Sturge Weber Syndrome - A case report with review of literature - Karthik Hegde; R Gopakumar; Subhas Babu; S Giridhar Naidu; Vidya Ajila; R Kamala (Wolters Kluwer Medknow Publications, 2007)
Sturge-Weber syndrome (SWS) belongs to a group of disorders collectively known as the phakomatoses ("mother-spot" diseases). It consists of congenital hamartomatous malformations that may affect the eye, skin, and central nervous system at different times. Sturge-Weber syndrome is rare. It is present at birth in about 1 in every 50,000 babies. SWS is classified into complete trisymptomatic SWS when all 3 organ systems are involved, incomplete bisymptomatic SWS when the involvement is either oculocutaneous or neurocutaneous, and incomplete monosymptomatic SWS when there is only neural or cutaneous involvement. Patients with no cutaneous involvement appear to be spared from the ocular manifestations of the syndrome. Presenting a case report of this rare disorder in a 26 year old male, who presented with lip enlargement.